2009
DOI: 10.1111/j.1440-1681.2009.05305.x
|View full text |Cite
|
Sign up to set email alerts
|

7‐difluoromethyl‐5,4′‐dimethoxygenistein, a novel agent protecting against vascular endothelial injury caused by oxidative stress

Abstract: 1. Genistein is known to protect the vascular endothelium. However, genistein exhibits poor bioavailability, which limits its use in the treatment of cardiovascular diseases. 7-Difluoromethyl-5,4'-dimethoxygenistein (dFMGEN), prepared by the difluoromethylation and alkylation of genistein, is a new active chemical entity. The protective effects of dFMGEN against vascular endothelial injury caused by oxidative stress were investigated in the present study. 2. Human umbilical vein endothelial cells were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Data suggested that DFMG possesses a protective effect against vascular endothelium injury caused by oxidative stress. Our team previously focused on the protective effects and mechanisms of DFMG as applied to the damaged endothelium 18,19,28,29. We had also previously revealed that DFMG has an antiatherosclerosis effect, decreasing hyperlipidemia and possessing antioxidant and plaque stabilization properties in a rabbit model of atherosclerosis 30.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggested that DFMG possesses a protective effect against vascular endothelium injury caused by oxidative stress. Our team previously focused on the protective effects and mechanisms of DFMG as applied to the damaged endothelium 18,19,28,29. We had also previously revealed that DFMG has an antiatherosclerosis effect, decreasing hyperlipidemia and possessing antioxidant and plaque stabilization properties in a rabbit model of atherosclerosis 30.…”
Section: Discussionmentioning
confidence: 99%